Exertional heat illness: international military-oriented lessons learned and best practices for prevention and management - Epstein, Yoram; Charkoudian, Nisha; DeGroot, David W.; House, Carol; Ketko, Itay; Law, Lydia Yu Li; Malgoyre, Alexandra; O’Connor, Francis; Tayari, Omar; Lee, Jason Kai Wei (Frontiers in Physiology, 2025)
Climate change has resulted in more frequent and intense heat waves, leading to elevated global temperatures and posing a significant health threat to individuals working in hot environments such as military personnel. Ensuring both safety and performance, alongside the increasing risk of exertional heat illnesses (EHI) due to rising temperatures, is hence even more crucial. Extensive research conducted over many years has aimed to understand the causes and impacts of EHI and develop prevention and treatment strategies. This review summarizes the research on the impacts of heat on health and performance in military settings, consolidates evidence-based strategies for EHI prevention and pre-hospital management, summarizes sex differences in heat tolerance, and discusses best practices for recovery and return to duty post-EHI. The aim is to share the knowledge and practices derived from military research to protect the health and performance of individuals in various populations exposed to heat.